Syarat Wajib Saksi dalam Perceraian dalam Tinjauan Maqashid Syariah, Mempertimbangkan Pandangan Fuqaha dan Mufassir - Andriyaldi, Andriyaldi; Nisa, Afdilla; Afifi, Abdullah A; Hamdani, Hamdani (IDRIS Darulfunun Institute, 2024)
Marriage in Islam is a sacred and strong bond that aims to maintain self-respect and create a harmonious family life. Islam pays great attention to preserving marriage and preventing rifts that can destroy family harmony. However, in conditions that cannot be maintained, Islam regulates a way out through divorce with wise provisions, including the requirement for witnesses. There are differences of opinion among scholars regarding the requirement of witnesses in divorce. Some scholars do not require witnesses in divorce, while others consider it mandatory. This article examines the background of these differences of opinion and then provides an analysis using the ushul fiqh and maqashid sharia approaches. This approach focuses on a deep understanding of the existing evidence and the use of evidence by scholars to support their opinions. By understanding the concept of maqashid sharia, we can see that the presence of witnesses in divorce is in line with the objectives of Islamic law and provides legal certainty. The obligation to have witnesses in divorce, as also stated in Indonesian Family Law, is a stronger view in maintaining justice and ensuring protection for all parties, especially in dealing with the impact of divorce on children and families.